Christianity and the Holocaust of Hungarian Jewry - Herczl, Moshe Y., 1924-1990.; Project Muse.; Project Muse. (New York, N.Y. : NYU Press, 1993)
The complicity of the Hungarian Christian church in the mass extermination of Hungarian Jews by the Nazis is a largely forgotten episode in the history of the Holocaust. Using previously unknown correspondence and other primary source materials, Moshe Y. Herczl recreates the church's actions and its disposition toward Hungarian Jewry. Herczl provides a scathing indictment of the church's lack of compassion toward--and even active persecution of--Hungary's Jews during World War II.
Preface and acknowledgments -- 1. The preparatory years -- Introduction -- Background -- The blood libel of Tisza Eszlar -- The Catholic people's party -- The revolutions and the white terror -- The Catholic press -- The "numerus clausus" law -- The consolidation of the twenties and the Christian antisemitism of the thirties -- Popular antisemitism of the thirties -- Cross movements and the Arrow-Cross party -- Conclusion -- 2. Anti-Jewish legislation -- Introduction -- The first anti-Jewish act -- The Eucharistic convention -- In the wake of the act's adoption -- The second anti-Jewish act -- The debate in the upper House: the stand of church leaders -- Extra-parliamentary activity during and after the debate on the second anti-Jewish act -- The demand for additional anti-Jewish legislation -- The third anti-Jewish act -- The Labor Battalions Act -- The Jewish Religion Status-Lowering Act -- The Jewish Estates Expropriation Act -- The Kallay Proposal for the expulsion of the Jews from Hungary -- Conclusion -- 3. 1944 -- Introduction -- The expulsion -- Who carried out the expulsion? -- Priestly activity -- The Shepherds' Epistles -- A quarter of a million Budapest Jews- Trapped -- Hungarian initiatives -- Conclusion -- Notes -- Index.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Holocaust, Jewish (1939-1945) -- Hungary; Christianity and antisemitism; Antisemitism -- Hungary -- History; Jews -- Hungary -- History; Hungary -- Ethnic relations; Electronic books